Association between disclosure quality and stock return with the moderating effects of corporate governance practices and ownership structure in Malaysia - Mohamad Anwar, Nazratul Aina (2015)
This study is motivated by three main study by Beretta and Bozzolan (2008), Bozzolan et al., (2009) and Wang and Hussainey (2013). Nevertheless, this study will extend their studies by specifically look into the quality effect of forward looking disclosure, stock return of the firm and proposing two moderating factors, namely ownership structure and corporate governance practices. Thus, objectives of this study are to investigate whether or not the disclosure, disclosure level, and disclosure quality of forward-looking information will significantly affect stock return of the firm. This study also proposed two moderating factors, namely corporate governance practices and ownership structure of the firm to ascertain whether these moderating factors can either weaken or strengthen the relationship between the disclosure quality of forwardlooking information and stock return of the firm. The sample in this study consists of 300 Malaysian public listed firms with the highest market capital in the Malaysian stock market from nine main industries listed on Bursa Malaysia in year 2013. Using modified abnormal return model, earnings-return model, and price model as valuation models to investigate the relationship between disclosure, disclosure level, and disclosure quality of forward-looking information on firm’s stock return, this study hypothesized that all of the disclosure effects will positive and significantly affects stock return of the firm. The proposed moderating factors are hypothesized to significantly moderate the relationship between disclosure quality of forward looking information and firm’s stock return. Based on cross sectional regression analysis, findings show that the disclosure and disclosure quality of forward looking information is positive and significantly related with firm’s stock return under earnings-return model. Corporate governance practices and ownership structure also play a significant role in moderating the relationship between disclosure quality of forward looking information and firm’s stock return. Both factors have strengthening the relationship based on findings that show the positive and significant relationship between interaction variables with firm’s stock return under abnormal return model at week 4 and price model respectively. However, relationship between disclosure level of forward-looking information and firm’s stock return is not significantly related in any of the valuation models. The empirical findings suggest that disclosure quality of forward-looking information is significant to improve firm’s stock return instead of focusing on the disclosure level of forward-looking information. From the findings, accounting standard setters and regulatory bodies could improve and make some renewal on corporate disclosure guide by outlining specific criteria of information that can be considered as quality information in preparing forward-looking statement and to promote corporate transparency. In addition, this result can contribute in assisting the family owned firms on how to entice back the attention of investors upon their perception towards information asymmetry issue caused by the agency problems that commonly exist in this type of ownership structure. At the same time, good corporate governance practices can be a better solution to attract investors’ attention towards the quality disclosure of forward-looking information to solve the information asymmetry issue and minimize the agency problems.